THE POSSIBILITIES OF PREDICTING PREMATURE DETACHMENT OF A NORMALLY LOCATED PLACENTA - Лазарева, Анна Юрьевна; Фаткуллина, Ирина Борисовна; Далаева, Танзила Хамидовна; Гареев, Евгений Мусинович (Mother and Baby in Kuzbass, 2024)
Obstetric bleeding associated with premature detachment of a normally located placenta occupies a leading position in the structure of massive bleeding, maternal and infant mortality, and is of increasing relevance due to the growth of pregnant women with a symptomatic complex of ischemic placental disease. Placental abruption is always a sudden and difficult-to-control situation, and the consequences are catastrophic, which is why it is so important to understand the predictors and predict this complication of the gestational process. Goal. A report on a new method for predicting the tendency to premature detachment of a normally located placenta (PPRP). Materials and methods. An antenatal examination was performed on 169 parameters reflecting various aspects of the condition of pregnant women. The Wald sequential analysis method was used to create a table that allows predicting the PPRP. Initially, using the Pearson criterion χ2 and the Fisher correlation coefficient (φ), the significance and degree of association of the occurrence of such states or gradations of the trait with the occurrence or absence of detachment were assessed. 16 parameters were selected for which the Fisher coefficient was significant and exceeded 0.35. For them, the calculation of the «odds ratio» (OR) and its 95% confidence limits was carried out, as well as the calculation of diagnostic coefficients for the presence or absence of a «risk factor». Results. The selected signs, considered as predictors of PPRP, were summarized in a prognostic table and provided with diagnostic coefficients. If the patient has a verifiable sign, DC+ is set, if it is absent, DC–. If the algebraic sum of these coefficients, taking into account the DC obtained on the basis of data on the prevalence of this disease, exceeds +9.8, then a 95% probability of a decision is made about the occurrence of placental abruption in a pregnant woman. If the total score is below -12.6, there will be no loss. If the sum of the coefficients is ≤ +9.8 and ≥ -12.6, then the forecast is invalid and no decision is made. Conclusion. This prognostic table is a «pilot project» and should be checked for validity in other patient samples in order to supplement and clarify. Nevertheless, it is for these purposes that it can be used as a tool for forming groups of pregnant women with a tendency to placental abruption and to carry out timely routing. During the study, the relationship between insulin resistance and placental abruption was revealed for the first time.